(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study has been carried out in Ponmalai hillock of Kanniyakumari District, Tamil Nadu, India, to document the floristic composition of the study area. Taxonomically, a total of 162 species belonging to 124 genera of 49 families of angiosperms were identified in the Ponmalai hillock of Kanniyakumari District, Tamil Nadu, India. Presently, the status of the Ponmalai hillock is deteriorating under constant anthropogenic pressure. Threat to Ponmalai hillock is discussed in this communication.